Inclusion education in an age of individualism - Bailey, Gerard J. (2017)
Inclusion is a term that, although seeming to have a commonly understood meaning, has changed its conceptual focus over the past 50 years. These changes emerge from the national shift in values and policy away from welfarism to post-welfarism and, more recently, austerity-as-ideology (Ignagni et al., 2015) - changes which have affected the societal territory, and the type of citizen into which inclusion is seen to be desirable. The effect on its application to primary schools has been to move away from a welfarist diversity discourse, in which opportunities were opened up for all children through a universalised education system, to the actuarial elitism of a standards discourse of post-welfarism, embodied in the form of National Curriculum learning expectations. It is the balancing of these two discourses within the context of three case-study primary schools that is the central focus of this research. It employs a mixed-method approach to gather data from children, staff and school leaders – including the use of photography to capture meanings of inclusion. It also uses a conceptual framework constructed from the canon of work of Pierre Bourdieu as the basis for interpreting and analysing the contextual uniqueness of inclusion within these schools. The research considers some overarching themes that arise from this analysis: inclusion as a means of social justice as it changed over the past 50 years to become synonymous with social mobility; the struggles of school leaders to find leadership pathways through the ‘tug’ of each discourse; the changing nature of citizenship and its effect upon inclusion as a means of induction into it and how this has impacted upon categorisations of children. Key to this has been the changing relationship between agent (child) and structure (school and government policy) with the latter currently demanding the compliance and conformity of the former. It is here that the current use of the term inclusion is misplaced, for it implies the integration of children into a structured system. It is this ‘messiness’ and confusion around the concept of inclusion that this research aims to clarify.